“Russia, Rossia, Rus, Kolomna: Province”: Conceptualization of Space in B. Pylnyak’s Novel “Volga Flows into Caspian Sea” - M. A. Dubova (Научный диалог)
The principles of structuring and methods of objectification of the spatial continuum in B. Pylnyak’s novel “The Volga flows into the Caspian Sea” are investigated. Particular attention is focused on the lexical representation of space as a basic category of the author’s language picture of the world. The novelty of the research consists in the identification, systematization and description of linguistic material, which allows to determine individual author’s features in the creation of the spatial continuum of B. Pylniak’s novel. The relevance of the article is due to addressing the problem of linguistic expression of world-modeling universals in a literary text. The article uses methods of semantic and linguistic stylistic analysis, comparison and description of language units. It helps us to identify and consider the means of lexical representation of the spatial model created in the novel “Volga Falls into Caspian Sea”, which is characterized by kaleidoscopicity, dynamism and the combination of different spatial planes. During the research, the author comes to conclusions containing the characteristics of the main types of space in B. Pylniak’s novel, taking into account the individual features of the author’s world modeling, as well as the substantiation of the revealed linguistic parameters of the writer’s idiostyle.